2008
DOI: 10.1029/2007ja012761
|View full text |Cite
|
Sign up to set email alerts
|

Multispacecraft and ground‐based observations of substorm timing and activations: Two case studies

Abstract: [1] Two case studies are performed to investigate substorm timing and activations based on Double Star TC1, Cluster, Polar, IMAGE, LANL geostationary satellites and ground-based geomagnetic field measurements. In both events, an earthward flow associated with plasma sheet thinning is measured by Cluster 8-10 min ahead of the auroral breakup. A couple of minutes after the breakup, either TC1 at $X-10 R E first detects plasma sheet expansion and then the LANL satellites near the midnight measure energetic electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 79 publications
3
24
0
3
Order By: Relevance
“…This indicates that the tail lobe reconnection took place somewhere earthward of these two probes, i.e. inside 16.5 R E (Cao et al, 2008). From 07:20 UT, the total pressure (in Fig.…”
Section: Cao Et Al: On the Retreat Of Near-earth Neutral Line Durmentioning
confidence: 85%
“…This indicates that the tail lobe reconnection took place somewhere earthward of these two probes, i.e. inside 16.5 R E (Cao et al, 2008). From 07:20 UT, the total pressure (in Fig.…”
Section: Cao Et Al: On the Retreat Of Near-earth Neutral Line Durmentioning
confidence: 85%
“…The earthward flowing high-speed flows can transport a large amount of magnetic flux that could lead to a magnetic field pileup [19][20][21]. Baumjohann et al [22] suggested that the dipolarization and the tailward retreat of the dipolarization region are due to the braking of the high-speed flows.…”
Section: High-speed Flows In Magnetic Convection and Substormsmentioning
confidence: 99%
“…Although the substorm expansion phase onset has been studied for decades, its trigger mechanism (e.g., cross-tail current disruption or magnetotail reconnection (MR)) remains controversial [Baker et al, 1996;Lui, 1996]. Greater understanding of both cross-tail current disruption and magnetotail reconnection is needed to resolve this controversy [Ohtani, 2001;Cao et al, 2008;Pu et al, 2010]. In this paper, we seek to better understand the processes leading to cross-tail current disruption.…”
Section: Introductionmentioning
confidence: 99%